PERANCANGAN APLIKASI E-VOTE BERBASIS MOBILE ANDROID PADA PEMILIHAN KETUA RT NGESTIHARJO RT 02/15 SISWODIPURAN BOYOLALI - Rizki Amelia; Saiful Bahri; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2018)
The title of this research is “ The Design of E-Vote Application based on Android Mobile”. The case of this study was on the Chairman Election in Ngestiharjo village, RT 02/15, Siswodipuran, Boyolali. This research held in Ngestiharjo village, RT 02/15, Siswodipuran, Boyolali. The research began since September 21st, 2015 until November 21st, 2015. The purpose of this research was to design a system for the Chairman Election in Ngestiharjo village, RT 02/15, Siswodipuran, Boyolali which can replace manual system of Chairman Election in RT 02/15. For developing the system of the research, we use Java programming language, Java usually used to make Android application. On this research, used MySQL database for database system. We use PIECES for the method of methodology which described by utilizing the methodology of UML (Unified Modelling Language). The method of Development System on this research we use Prototyping method. For data gathering process, we use quantitative method (observation, interview and study literature). The conclusion of this research is RT-Vote Application can be one of solution to help the Chairman Election process in Ngestiharjo village, RT 02/15, Siswodipuran, Boyolali. In the research, we still have a problem in connecting the database with the RT-Vote Application. So, this research still required some reparation on the database of RT- Vote Application.